The Existence of Gayo Marriage Culture and Costums in Banda Aceh - Fitriana*, Fitriana; Maulida, Dinda; Nurbaiti, Nurbaiti; Rahmi, Rahmi (Universitas Syiah Kuala, 2024)
Culture and customs are habbits that have prevailed between generation in a society whose existence function as a guideline for thinking and acting in that society. The Gayo community who live in Banda Aceh combines the culture and costums of Gayo marriage with the costoms and culture of Coastal Aceh, so it is necessaary to study how its existence continus today. The purpose of this study was to determine the existence of the Gayo marriage customs held in Banda Aceh, identify the stages or processions of the Gayo marriage ceremony, and determine the influence of other cultures on Gayo marriage customs in Banda Aceh. The subjects in this study amounted to 4 people consisting of 3 people who carried out the marriage procession and 1 Gayo traditional leader. The results showed that the stages of the Gayo traditional wedding ceremony procession in Banda Aceh consisted of: the process of pre-wedding activities consisting of 4 parts: kusik, sisu, pakok, and paden; wedding preparations are divided into six parts: risk, resek, rise, kono, kite and teniron; the implementation of the marriage is divided into eight parts; studying, giving up, bejege, mah bai, beru, ukum deliberation, dalem ceremony and reckoning mas. The ceremony after the wedding consists of 2 parts, mah beru and mah kero. Of all these stages, there are several stages that accompany the Aceh Pesisir wedding customs such as the night of berinai, peusijuk, exchange of batil (betel places), eating besan on the day of the reception (eating with the bride's family), headdresses and aisle colors which tend to be bright colors. The bride and groom have held a traditional Gayo wedding ceremony in Banda Aceh and this happened because of the influence of the culture of the residents with various tribes living in one area.